THE DIGITAL BANKING BASED OF ZISWAF FUNDRAISING AND FUND MANAGEMENT IN SHARIA ECONOMIC LAW PERSPECTIVE (Study at PT. BSI KCP Bandar Lampung Teluk Betung) - Nita Yuliza; Zuhraini; Kumedi Ja’far; Liky Faizal (Jurnal ini dipublikasikan oleh Pusat Penelitian dan Pengabdian Publikasi (P3M) STAI Nahdlatul Watan Samawa-licensed under a Creative Commons Attribution-ShareAlike 4.0 International License., 2022)
Digital banking services in Islamic banking continue to progress and improve. Digital banking services can ease Sariah Bank customers to transact by only using a mobile phone in 24-hour service. One of the digital banking services in Islamic banking is ZISWAF fundraising and fund management. ZISWAF is one of the products that will be the focus of the company in business development in the future because ZISWAF is a source of funds for Muslims who are expected to realize prosperity, social justice and reduce poverty. In order to increase the potential of zakat in Indonesia, the National Amil Zakat Agency has officially appointed the Zakat Management Unit (UPZ) of Bank Syar'ah Indonesia by utilizing digital banking. Therefore, this research was conducted to find out how the Sharia Economic Law Perspective towardThe Digital Banking Based of ZISWAFfundraising and fund management at PT. BSI KCP Bandar Lampung TelukBetung. The results of the field research show that ZISWAF fundraising based on digital banking uses the BSI Mobile platform, BSI ATM, and the Jadiberkah.id platform. About fund management, ZISWAF funds are managed through charity programs and sustainable programs. If it is viewed from the perspective of Sharia Economic Law, The Digital Banking Based of ZISWAF fundraising andfund managementis legal because it is included in providing convenience benefits, as explained in the surat Al-A̒lᾱ [87]: 8 The paragraphs explain that Allah SWT provides convenience for everyone. Muslims to get a way of convenience (in all matters) and have the value of benefit and be able to maintain the interests or objectives of Islamic law and are maṣlaḥah al-ḥᾱjjiyah, namely making it easier for BSI customers in paying ZISWAF and easing in worship.